Therapeutic Effects of Intranasal Administration of Mesenchymal Stem Cell-Derived Secretome in Rats Exposed to Chronic Unpredictable Mild Stress - Ortiz-Cisternas, F (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Background: Major depression is a significant source of suffering and economic loss. Despite efforts to understand this condition and find better treatments, the burden imposed by this disease continues to rise. Most approved pharmacological treatments for depression focus on controlling the availability of monoamines in synapses. However, accumulating evidence suggests that neuroinflammation, oxidative stress, and reduced hippocampal neurogenesis play key roles as causal factors in the development of major depression symptoms. Therefore, preclinical testing of pharmacological approaches targeting these factors is essential. Mesenchymal stem cells (MSCs) are known for their potential as powerful antioxidants and anti-inflammatory agents, exerting neuroprotective actions in the brain. They produce various therapeutic molecules in a paracrine manner, collectively known as secretome. Methods: In this work, we evaluated the antidepressant potential of repeated intranasal administration of MSC-derived secretome in an animal model of major depressive disorder induced by chronic mild unpredictable stress. Results: We observed that intranasal administration of MSC-derived secretome reduced the appearance of some of the behavioral parameters commonly associated with major depression, including anhedonic, apathetic, and anxious behaviors, inducing a strong reduction in the overall depression score compared to vehicle-treated animals. At the structural level, secretome administration prevented increased astrocyte density and the atrophy of astrocyte processes observed in vehicle-treated stressed animals. Additionally, secretome administration induced an increase in myelin levels and oligodendroglia in the cortex. Conclusions: Our data suggests that intranasal administration of MSC-derived secretome may represent a potential therapeutic alternative to current treatments for this devastating pathology. © 2025 by the authors.